(3QSGdI HOA GdNdbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Edg GdMb heHOY YdI GdNdb Ef CMSf eG CHJOF Hg MeO GdHGQ GdeRg Yf GdCRd hGdCRdjI HeG Ndbg Yf Ndbg HMceJg GdYdjI s
(3BNQgG (B:s
(3hehai cd Ceg CLdgG HYO EbGeI GdMLL Ydi fahS CTNGUgG JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdMb YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B85s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis